Health profile of people living in the Gare Palma mining area of Tamnar block, Raigarh, Chhattisgarh, India - Shrivastava, Suyesh; Kumar, Ravindra; Khan, Sirin; Kavishwar, Arvind; Gupta, Ashok; Kaur, Harpreet; Das, Madhuchanda; Sharma, Ravendra; Chakma, Tapas (Frontiers in Public Health, 2023)
Introduction A community-based health survey was conducted in Tamnar block, Raigarh district of Chhattisgarh, India. Methodology A total of 909 individuals (adults) were selected from 909 households from 33 sampled villages from March 2019 to February 2020. All individuals were clinically examined, and observations were recorded. Results Among adults older than 18 years, hypertension was observed in 21.7%. Type II diabetes was observed in only 4.0% of individuals. Tuberculosis was seen in 23 (2.5%) individuals. Discussion Common morbidities were similar in tribal and non-tribal communities living in the same area. For communicable diseases, being male, having nutritional deficiencies, and smoking were independent risk factors. For non-communicable diseases, the independent significant risk factors identified were being male, an altered body mass index, disturbed sleep, smoking, and nutritional deficiencies.